2009
DOI: 10.1007/s12010-009-8724-7
|View full text |Cite
|
Sign up to set email alerts
|

A Multistage Process to Enhance Cellobiose Production from Cellulosic Materials

Abstract: Cellobiose, a disaccharide, is a valuable product that can be obtained from cellulose hydrolysis. In this study, a simple methodology is presented to enhance the production and improve the selectivity of cellobiose during enzymatic hydrolysis of cellulose. The approach consisted of a multistage removal of filtrate via vacuum filtration and resuspension of the retentate. By this process, the remaining solid was further hydrolyzed without additional enzyme loading. Compared to the continuous hydrolysis process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Usually, b-glucosidase in the cellulase complex is responsible for the conversion of cellobiose into glucose. It is possible to control cellulose hydrolysis to accumulate more cellobiose over glucose (Homma et al, 1993;Vanderghem et al, 2009;Kim and Day, 2010), and production of ethanol from cellobiose has been demonstrated using yeast strains heterologously expressing b-glucosidase (Vanrooyen et al, 2005;Gurgu et al, 2011). Also, cellobiose and xylose co-fermentation has been used to produce ethanol (Nakamura et al, 2008;Saitoh et al, 2010;Li et al, 2010;Ha et al, 2011).…”
Section: Lipid Production By L Starkeyi On Cellobiose Glucose or Xymentioning
confidence: 99%
“…Usually, b-glucosidase in the cellulase complex is responsible for the conversion of cellobiose into glucose. It is possible to control cellulose hydrolysis to accumulate more cellobiose over glucose (Homma et al, 1993;Vanderghem et al, 2009;Kim and Day, 2010), and production of ethanol from cellobiose has been demonstrated using yeast strains heterologously expressing b-glucosidase (Vanrooyen et al, 2005;Gurgu et al, 2011). Also, cellobiose and xylose co-fermentation has been used to produce ethanol (Nakamura et al, 2008;Saitoh et al, 2010;Li et al, 2010;Ha et al, 2011).…”
Section: Lipid Production By L Starkeyi On Cellobiose Glucose or Xymentioning
confidence: 99%
“…The multistage hydrolysis (four times, 6 h) for both celluloses was performed according to the procedure of Vanderghem et al [11]. Celluloses were suspended at a concentration of 50 g/L in citrate buffer.…”
Section: Water Retention Valuementioning
confidence: 99%
“…In a previous study, cellulose enzymatic hydrolysis was investigated in a multistage process to enhance the cellobiose production of a cellulose fiber [11]. In this study, two more types of cellulose, varying in crystallinity and particle size (microcrystalline cellulose and paper pulp), were evaluated for the production of cellobiose under the multistage process.…”
Section: Introductionmentioning
confidence: 99%
“…The practical amylose yield could be enhanced through more cellobiose production by optimizing the cellulase mixture composition and ratio, eliminating beta-glucosidase from the commercial cellulase mixtures, optimization of CBP-PGP loading, improving PGP performance, process design (47), and biomass pretreatment conditions. For potential application, the current amylose yields (e.g., 2-30%) in biorefineries would be acceptable because no sugar is wasted and the potential market for synthetic starch as food and feed could be less than 1/10th that of biofuels and biochemicals (4,48).…”
Section: Discussionmentioning
confidence: 99%